A degradable, anti-swelling high-strength polyvinyl alcohol hydrogel and a preparation method thereof

CN122978477APending Publication Date: 2026-10-27曾庆松
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611128564.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-28
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

虽然该类复合水凝胶能够改善细胞黏附性、生物相容性及体内降解性能,但由于上述可降解聚合物普遍具有较高的亲水性,材料在吸水后容易发生明显溶胀,导致体积膨胀、力学性能下降、尺寸稳定性变差,并进一步影响材料在组织修复、长期植入及药物缓释过程中的使用性能

Benefits of technology

1、本发明构建了物理交联与化学交联协同作用的双重网络结构,显著提高了聚乙烯醇水凝胶的力学性能及结构稳定性。本发明首先利用冷冻与溶剂相转变诱导聚乙烯醇链形成纳米微晶物理交联网络,再通过紫外光诱导巯基-烯点击化学反应构建稳定的共价交联网络,最后结合牵伸热定型进一步提高聚合物链取向度和结晶程度,实现了物理交联、化学交联及链取向增强的协同作用,使所得水凝胶具有更高的拉伸强度、断裂伸长率及抗疲劳性能,能够满足软骨修复、骨组织工程及长期植入等应用对高强度生物材料的需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122978477A_ABST
    Figure CN122978477A_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of high molecular hydrogel material, and particularly relates to a degradable and anti-swelling high-strength polyvinyl alcohol hydrogel and a preparation method thereof. The present application takes thiol-modified polyvinyl alcohol as a network main chain, and takes degradable polymer modified by an acrylate group as a crosslinking agent. Firstly, the system is made into a nano-microcrystalline crosslinked primary hydrogel under the condition of freezing and solvent phase transition. Then, a stable chemical crosslinking network is formed through a thiol-ene click chemistry reaction by ultraviolet irradiation. Finally, the hydrogel is stretched and heat set in the stretched state, so as to improve the polymer chain orientation degree and crystallization degree, thereby obtaining a polyvinyl alcohol hydrogel material which has the properties of degradability, anti-swelling, high strength and excellent biocompatibility. The obtained hydrogel can be widely applied in the fields of cartilage / bone tissue engineering, skin wound dressing and long-acting drug release.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of synthetic materials technology, and in particular to a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel and its preparation method. Background Technology

[0002] Polyvinyl alcohol (PVA) is a polymer material with excellent biocompatibility, biosafety, hydrophilicity, film-forming properties, and mechanical properties, and is widely used in tissue engineering, biomedical materials, drug delivery, wound dressings, and flexible electronic devices. Because PVA molecules are rich in hydroxyl groups, they can form three-dimensional network structures through repeated freeze-thaw cycles, chemical cross-linking, and radiation cross-linking. Therefore, PVA hydrogels have become one of the most widely studied biomedical hydrogel materials.

[0003] Currently, polyvinyl alcohol (PVA) hydrogels are mainly classified into two types: physically crosslinked and chemically crosslinked. Physically crosslinked PVA hydrogels typically use freeze-thaw cycles to induce the formation of microcrystalline regions from PVA segments as physical crosslinking points, eliminating the need for chemical crosslinking agents and thus exhibiting better biocompatibility. However, this type of hydrogel relies primarily on hydrogen bonds and crystalline regions to maintain its network structure. Under prolonged immersion or stress conditions, it is prone to microcrystalline dissociation and network relaxation, leading to a decline in mechanical properties. Furthermore, the high number of freeze-thaw cycles and long preparation time make it difficult to meet the demands for rapid preparation and the molding of complex structures.

[0004] In contrast, chemically cross-linked polyvinyl alcohol hydrogels can form stable covalent cross-linked networks using cross-linking agents such as glutaraldehyde, borates, epoxy compounds, and isocyanates, exhibiting higher structural stability and mechanical properties. However, existing chemical cross-linking systems generally suffer from problems such as demanding cross-linking reaction conditions, potential cytotoxicity of some cross-linking agents, limited cross-linking efficiency, and difficulty in achieving rapid in-situ curing, which hinders their further application in tissue engineering and biomedical fields.

[0005] In recent years, with the development of click chemistry, the thiol-ene click reaction has been increasingly applied to the construction of biomedical hydrogels due to its advantages such as fast reaction speed, mild reaction conditions, high selectivity, small oxygen inhibition effect, and high crosslinking efficiency. By introducing thiol and alkenyl groups onto the polymer chain, a uniform and stable three-dimensional crosslinked network can be rapidly formed under ultraviolet light irradiation, enabling rapid molding and in-situ curing of hydrogels. However, research on the construction of polyvinyl alcohol hydrogels using the thiol-ene click reaction is still relatively limited. Most systems still employ a single chemical crosslinking method, resulting in limited network structure uniformity and difficulty in simultaneously achieving high strength, rapid crosslinking, and long-term stability.

[0006] On the other hand, to endow polyvinyl alcohol hydrogels with good biodegradability, researchers often construct dual-network systems by combining polyvinyl alcohol with natural or synthetic biodegradable polymers such as gelatin, hyaluronic acid, alginate, chitosan, silk fibroin, and polyethylene glycol. Although such composite hydrogels can improve cell adhesion, biocompatibility, and in vivo degradation performance, the high hydrophilicity of these biodegradable polymers means that the materials tend to swell significantly after absorbing water, leading to volume expansion, decreased mechanical properties, and poor dimensional stability. This further affects the material's performance in tissue repair, long-term implantation, and drug sustained-release processes.

[0007] Furthermore, most publicly available polyvinyl alcohol (PVA) composite hydrogels currently rely on single chemical or physical crosslinking methods to form a network structure. This results in limited crosslinking density, disordered polymer chain arrangement, and low internal crystallinity, leading to insufficient tensile strength, fatigue resistance, and dimensional stability to meet the high-performance application requirements for cartilage repair, bone tissue engineering, and long-term implantation. Simultaneously, because PVA itself is a recalcitrant polymer, its traditional crosslinking network is difficult to degrade in a controlled manner, limiting its further application in in vivo implant materials.

[0008] Therefore, how to construct a polyvinyl alcohol hydrogel that combines rapid cross-linking, anti-swelling, high mechanical properties, controllable degradation, and excellent biocompatibility remains an important technical problem that needs to be solved by those skilled in the art.

[0009] To address the problems existing in the prior art, this invention provides a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel and its preparation method. By functionalizing polyvinyl alcohol with thiol groups and introducing a biodegradable polymer modified with acrylate groups as a crosslinking agent, combined with freeze-solvent phase transition induction to form a nanocrystalline physical crosslinking network, UV-induced thiol-olefin click reaction to construct a chemical crosslinking network, and stretching and heat setting to promote polymer chain orientation and crystallinity, a synergistic effect of physical and chemical crosslinking is achieved. This results in significantly improved mechanical properties, swelling resistance, and structural stability of the material while maintaining excellent biocompatibility, and endows it with controllable biodegradability, thereby meeting the application needs in biomedical fields such as tissue engineering scaffolds, wound repair materials, and drug delivery carriers. Summary of the Invention

[0010] To solve the above-mentioned technical problems, the present invention provides the following technical solution: a degradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel, which is prepared from polyvinyl alcohol, a degradable polymer, and a photoinitiator; polyvinyl alcohol reacts with a mercapto reagent; the degradable polymer reacts with an acrylate-based reactive reagent; polyvinyl alcohol, the degradable polymer, and the photoinitiator are mixed, dissolved, solidified, and subjected to rapid photocrosslinking under ultraviolet light irradiation, and then stretched, heat-set, and washed to obtain the polyvinyl alcohol hydrogel.

[0011] A method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel includes the following steps: S1, preparation of thiol-modified polyvinyl alcohol: dissolve polyvinyl alcohol in a solvent to prepare a polyvinyl alcohol solution, then add a thiol-modifying reagent and react under the catalysis of an acidic reagent to obtain thiol-modified polyvinyl alcohol.

[0012] S2. Preparation of acrylate-modified biodegradable polymers: Dissolve the biodegradable polymer in a good solvent to prepare a solution, stir mechanically until completely dissolved, add acrylate-modified reagents dropwise, stir mechanically until the reaction is complete, pour the reaction solution into a poor solvent for washing, and dry to obtain acrylate-modified biodegradable polymers.

[0013] S3. Preparation of hydrogel: The modified polyvinyl alcohol, biodegradable polymer, photoinitiator and good solvent are added into a stirred tank in proportion, heated and mechanically stirred until completely dissolved, filtered under pressure, and the filtrate is squeezed into a degassing tank and degassed under vacuum to obtain a homogeneous solution. The homogeneous solution is poured into a rectangular mold and placed in a coagulation bath to solidify and form. Then, it is rapidly photocrosslinked by ultraviolet light irradiation. Finally, after stretching, heat setting and washing, a high-strength polyvinyl alcohol hydrogel that is biodegradable and rapidly photocrosslinkable is obtained.

[0014] In a preferred embodiment of the present invention, the polyvinyl alcohol has a dissolution temperature of 20–250°C and a polyvinyl alcohol solution concentration of 0.5%–80%; the solvent includes one or more of water, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide; the thiolation reagent includes γ-thiobutyrolactone, δ-thiovalactone, ε-thiocaprolactone, homocysteine ​​thiolactone, α-lipoic acid, 3,3'-dithiodipropionic acid, cyclic thiocarbonate, thiosuccinic anhydride, and protected thiolactone. One or more dithiolactones; acidic reagents include one or more of sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, camphorsulfonic acid, hydrochloric acid, phosphoric acid, and perchloric acid; the molar ratio of the thiol-modified reagent solution and the acidic reagent solution to the hydroxyl groups of the polyvinyl alcohol side chain is 0.0001–1, and the concentration is 1%–70%; the molecular weight of the thiol-modified polyvinyl alcohol is 6000–200000, the degree of alcoholysis is 60%–100%, and the concentration of the thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition is 1%–90%; good solvents include water, DMF, and DMAc. One or more of NMP and DMSO; biodegradable polymers include one or more of gelatin, hyaluronic acid, sodium alginate oxide, poloxamer, silk fibroin, dextran, chitosan, and polyethylene glycol; the concentration of the solution prepared by dissolving the biodegradable polymer in a good solvent is 0.5%–80%; acrylate-based reactive reagents include one or more of methacrylic anhydride, acrylic anhydride, methacryloyl chloride, acryloyl chloride, cinnamoyl chloride, and glycidyl methacrylate; the acrylate-based reactive reagents can be modified with the side chains of the biodegradable polymer. The molar ratio of the modified groups is 0.0001–1, and the concentration is 1%–70%; unsuitable solvents include one or more of n-hexane, cyclohexane, petroleum ether, toluene, dichloromethane, chloroform, ethyl acetate, diethyl ether, acetone, ethanol, and ethylene glycol; the molar ratio of acrylate-based reactants to modifiable groups on the side chains of the biodegradable polymer is 0.0001–1, and the concentration is 1%–70%; the concentration of the acrylate-modified biodegradable polymer in the polyvinyl alcohol composition is 0.5%–30%; the photoinitiator includes Irgacure. One of the following is used: 2959, Irgacure 1173, riboflavin RF, eosin EY (tetrabromofluorescein), lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), and sodium phenyl-2,4,6-trimethylbenzoylphosphonate (NAP), in an amount of 0.005wt%~5wt% of the mass of the mercapto-modified polyvinyl alcohol; the temperature of the filtrate extruded into the degassing kettle is set to 0~200℃, and the vacuum degassing time is 1h~72h; the coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and the temperature of the coagulation bath is -60~70℃; the ultraviolet light configuration is a wavelength of 200~400nm, an intensity of 20~150W, and an ultraviolet light irradiation time of 5s~180s; the stretching is 0.The heat setting temperature is 20–300℃, and the washing temperature is 10–100℃. (The formula is incomplete and requires further context.)

[0015] As a preferred embodiment of the present invention, the polyvinyl alcohol has a dissolution temperature of 40–150°C, and the concentration of the prepared polyvinyl alcohol solution is 1%–40%; the thiol-modified polyvinyl alcohol has a molecular weight of 80,000–170,000, a degree of alcoholysis of 70%–99%, and a concentration of thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition of 10%–60%; the concentration of the acrylate-modified biodegradable polymer in the polyvinyl alcohol composition is 1%–20%; the amount of photoinitiator is 0.5%–2% of the mass of the thiol-modified polyvinyl alcohol; and the filtrate is extruded… The temperature in the degassing kettle is set to 40–150℃, and the vacuum degassing time is 3–10 h; the coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and the coagulation bath temperature is -40–20℃; the ultraviolet light is configured with a wavelength of 200–400 nm, an intensity of 50–100 W, and an ultraviolet light irradiation time of 10–120 s; the stretching is 1–30 times, the heat setting temperature is 80–200℃, and the water washing temperature is 50–90℃.

[0016] In a preferred embodiment of the present invention, the polyvinyl alcohol has a dissolution temperature of 80–100°C and a concentration of 5%–15% in the prepared polyvinyl alcohol solution; the thiolated reagent is γ-thiobutyrolactone; the acidic reagent is sulfuric acid; the molar ratio of the thiolated reagent solution and the acidic reagent solution to the hydroxyl groups on the side chain of the polyvinyl alcohol is 0.01–0.5, and the concentration is 10%–30%; the thiolated polyvinyl alcohol has a molecular weight of 120,000–150,000, a degree of alcoholysis of 90%–97%, and a concentration of thiolated polyvinyl alcohol in the polyvinyl alcohol composition of 20%–40%; the good solvent is water, and the concentration of the solution prepared by dissolving the degradable polymer in the good solvent is 1%–20%; the acrylate group reaction reagent is methacryloyl chloride; the molar ratio of the acrylate group reaction reagent to the modifiable groups on the side chain of the degradable polymer is 0.01–0.5, and the concentration is 5%–30%; the concentration of the acrylate group-modified degradable polymer in the polyvinyl alcohol composition is 5%–10%; and the photoinitiator is Irgacure. 2959, the dosage is 0.8% to 1.5% of the mass of mercapto-modified polyvinyl alcohol; the temperature of the filtrate extruded into the degassing kettle is set at 60 to 90℃, and the vacuum degassing time is 6h to 24h; the coagulation bath component is ethylene glycol monomethyl ether, and the coagulation bath temperature is -30 to -10℃; the ultraviolet light configuration is wavelength 365nm, intensity 80W, and ultraviolet light irradiation time is 30s to 90s; the stretching is 5 to 10 times, the heat setting temperature is 140 to 180℃, and the water washing temperature is 80 to 95℃.

[0017] Compared with the prior art, the beneficial effects that this invention can achieve are: 1. This invention constructs a dual network structure with synergistic effects of physical and chemical crosslinking, significantly improving the mechanical properties and structural stability of polyvinyl alcohol hydrogels. First, this invention utilizes freezing and solvent phase transition to induce the formation of a nanocrystalline physical crosslinking network of polyvinyl alcohol chains. Then, it constructs a stable covalent crosslinking network through ultraviolet light-induced click chemistry of thiol-olefins. Finally, it combines stretching and heat setting to further enhance the polymer chain orientation and crystallinity. This achieves a synergistic effect of physical crosslinking, chemical crosslinking, and chain orientation enhancement, resulting in a hydrogel with higher tensile strength, elongation at break, and fatigue resistance, meeting the demands for high-strength biomaterials in applications such as cartilage repair, bone tissue engineering, and long-term implantation.

[0018] 2. This invention effectively reduces the swelling rate of the hydrogel, improving the dimensional stability and long-term service performance of the material. This invention uses a biodegradable polymer modified with acrylate groups as a crosslinking agent. A uniform and dense three-dimensional crosslinked network is formed through a mercapto-olefin click reaction. Combined with the physical confinement effect of polyvinyl alcohol nanocrystal regions, the free movement of polymer chain segments is effectively restricted, reducing excessive water absorption and network over-expansion. This results in a hydrogel with excellent anti-swelling properties, maintaining good dimensional and mechanical stability even during long-term immersion, tissue fluid environments, and drug sustained-release processes.

[0019] 3. The preparation process of this invention is simple and efficient, and the resulting hydrogel possesses rapid molding, controllable degradation, and excellent biocompatibility, showing promising prospects for industrial application. This invention utilizes ultraviolet light-induced thiol-olefin click chemistry to achieve rapid cross-linking and molding of the hydrogel. The cross-linking speed is fast, the reaction conditions are mild, and the cross-linking efficiency is high. Simultaneously, a biodegradable polymer is introduced as a cross-linking component, enabling the resulting hydrogel to maintain high mechanical properties while possessing controllable biodegradability, as well as high cell compatibility and biosafety. It can be widely used in cartilage and bone tissue engineering, skin wound repair, drug sustained release, biomedical dressings, and other biomedical materials, demonstrating high clinical application value and promising prospects for industrialization. Attached Figure Description

[0020] Figure 1 This is a schematic diagram of the method flow of the present invention. Detailed Implementation

[0021] To make the technical means, creative features, and achieved objectives and effects of this invention easier to understand, the invention is further described below with reference to specific embodiments. However, the following embodiments are merely preferred embodiments of this invention and not all of them. Other embodiments or implementations obtained by those skilled in the art based on the embodiments or implementations described in the specific embodiments without creative effort are all within the protection scope of this invention.

[0022] Example A: A biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel is prepared from polyvinyl alcohol, a biodegradable polymer, and a photoinitiator. Polyvinyl alcohol is reacted with a mercapto reagent; the biodegradable polymer is reacted with an acrylate-based reactive reagent; polyvinyl alcohol, the biodegradable polymer, and the photoinitiator are mixed, dissolved, solidified, and subjected to rapid photocrosslinking under ultraviolet light irradiation, and then stretched, heat-set, and washed to obtain the polyvinyl alcohol hydrogel.

[0023] A method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel includes the following steps: S1. Preparation of mercapto-modified polyvinyl alcohol: Polyvinyl alcohol is dissolved in a solvent to prepare a polyvinyl alcohol solution.

[0024] The polyvinyl alcohol has a dissolution temperature of 20–250°C and a concentration of 0.5%–80% in the prepared polyvinyl alcohol solution. The solvent includes one or more of water, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0025] Subsequently, a thiol-modified reagent was added and, under the catalysis of an acidic reagent, thiol-modified polyvinyl alcohol was obtained.

[0026] The thiolation reagents include one or more of γ-thiobutyrolactone, δ-thiovalactone, ε-thiocaprolactone, homocysteine ​​thiolactone, α-lipoic acid, 3,3'-dithiodipropionic acid, cyclic thiocarbonate, thiosuccinic anhydride, protected thiolactone, and dithiolactone.

[0027] The acidic reagent includes one or more of sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, camphorsulfonic acid, hydrochloric acid, phosphoric acid, and perchloric acid; the molar ratio of the thiol-modified reagent solution and the acidic reagent solution to the hydroxyl side chain of polyvinyl alcohol is 0.0001 to 1, and the concentration is 1% to 70%; the molecular weight of the thiol-modified polyvinyl alcohol is 6,000 to 200,000, the degree of alcoholysis is 60% to 100%, and the concentration of the thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition is 1% to 90%.

[0028] S2. Preparation of acrylate-modified biodegradable polymers: Dissolve the biodegradable polymer in a good solvent to prepare a solution.

[0029] The good solvent includes one or more of water, DMF, DMAc, NMP, and DMSO; the degradable polymer includes one or more of gelatin, hyaluronic acid, sodium alginate, poloxamer, silk fibroin, dextran, chitosan, and polyethylene glycol, and the concentration of the solution prepared by dissolving the degradable polymer in the good solvent is 0.5% to 80%.

[0030] Stir mechanically until completely dissolved, add acrylate-based reaction reagent dropwise, stir mechanically until the reaction is complete, and then wash the reaction solution in a poor solvent.

[0031] The acrylate-based reaction reagents include one or more of methacrylic anhydride, acrylic anhydride, methacryloyl chloride, acryloyl chloride, cinnamoyl chloride, and glycidyl methacrylate; the molar ratio of the acrylate-based reaction reagents to the modifiable groups on the side chains of the degradable polymer is 0.0001 to 1, and the concentration is 1% to 70%; the unsuitable solvents include one or more of n-hexane, cyclohexane, petroleum ether, toluene, dichloromethane, chloroform, ethyl acetate, diethyl ether, acetone, ethanol, and ethylene glycol.

[0032] A biodegradable polymer modified with acrylate groups was obtained by drying.

[0033] The molar ratio of acrylate-based reaction reagents to modifiable groups on the side chains of biodegradable polymers is 0.0001–1, and the concentration is 1%–70%; the concentration of biodegradable polymers modified with acrylate-based groups in the polyvinyl alcohol composition is 0.5%–30%.

[0034] S3. Preparation of hydrogel: The modified polyvinyl alcohol, biodegradable polymer, photoinitiator and good solvent are added into a stirred tank in proportion and heated and mechanically stirred until completely dissolved.

[0035] The photoinitiator includes one of Irgacure 2959, Irgacure 1173, riboflavin RF, eosin EY (tetrabromofluorescein), lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), and sodium phenyl-2,4,6-trimethylbenzoylphosphonate (NAP), and is used in an amount of 0.1% to 5% of the mass of the mercapto-modified polyvinyl alcohol. The liquid is pressurized and filtered, then squeezed into a degassing vessel and degassed under vacuum to obtain a homogeneous colloid.

[0036] The temperature of the filtrate squeezed into the degassing kettle is set to 0-200℃, and the vacuum degassing time is 1h-72h.

[0037] Pour the homogeneous adhesive liquid into a rectangular mold and place it in a coagulation bath to solidify and shape.

[0038] The coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether; the temperature of the coagulation bath is -60 to 70°C; the ultraviolet light is configured with a wavelength of 200 to 400 nm, an intensity of 20 to 150 W, and an ultraviolet light irradiation time of 5 to 180 s.

[0039] Subsequently, rapid photocrosslinking is performed by irradiation with ultraviolet light. Finally, after stretching, heat setting and washing, a biodegradable and rapidly photocrosslinkable high-strength polyvinyl alcohol hydrogel is obtained.

[0040] The stretching is 0.1 to 50 times, the heat setting temperature is 20 to 300℃, and the washing temperature is 10 to 100℃.

[0041] Example B: In this embodiment, the raw materials, basic steps, and post-processing methods for preparing the hydrogel are the same as in Example A. The only difference is that the preparation parameters have been adjusted. Unless otherwise specified, all contents refer to Example A.

[0042] Specifically, a method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel includes the following steps: S1. Preparation of mercapto-modified polyvinyl alcohol: Polyvinyl alcohol is dissolved in a solvent to prepare a polyvinyl alcohol solution.

[0043] The polyvinyl alcohol has a dissolution temperature of 40–150°C and a concentration of 1%–40% in the prepared polyvinyl alcohol solution. The solvent includes one or more of water, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0044] Subsequently, a thiolizing agent was added in situ and reacted under the catalysis of an acidic reagent to obtain thiol-modified polyvinyl alcohol.

[0045] The thiolation reagents include one or more of γ-thiobutyrolactone, δ-thiovalactone, ε-thiocaprolactone, homocysteine ​​thiolactone, α-lipoic acid, 3,3'-dithiodipropionic acid, cyclic thiocarbonate, thiosuccinic anhydride, protected thiolactone, and dithiolactone.

[0046] The acidic reagent includes one or more of sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, camphorsulfonic acid, hydrochloric acid, phosphoric acid, and perchloric acid; the molar ratio of the thiol-modified reagent solution and the acidic reagent solution to the hydroxyl side chain of polyvinyl alcohol is 0.0001 to 1, and the concentration is 1% to 70%; the molecular weight of the thiol-modified polyvinyl alcohol is 80,000 to 170,000, the degree of alcoholysis is 70% to 99%, and the concentration of the thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition is 10% to 60%.

[0047] S2. Preparation of acrylate-modified biodegradable polymers: Dissolve the biodegradable polymer in a good solvent to prepare a solution.

[0048] The good solvent includes one or more of water, DMF, DMAc, NMP, and DMSO; the degradable polymer includes one or more of gelatin, hyaluronic acid, sodium alginate, poloxamer, silk fibroin, dextran, chitosan, and polyethylene glycol, and the concentration of the solution prepared by dissolving the degradable polymer in the good solvent is 0.5% to 80%.

[0049] Stir mechanically until completely dissolved, add acrylate-based reaction reagent dropwise, stir mechanically until the reaction is complete, and then wash the reaction solution in a poor solvent.

[0050] The acrylate-based reaction reagents include one or more of methacrylic anhydride, acrylic anhydride, methacryloyl chloride, acryloyl chloride, cinnamoyl chloride, and glycidyl methacrylate; the molar ratio of the acrylate-based reaction reagents to the modifiable groups on the side chains of the degradable polymer is 0.0001 to 1, and the concentration is 1% to 70%; the unsuitable solvents include one or more of n-hexane, cyclohexane, petroleum ether, toluene, dichloromethane, chloroform, ethyl acetate, diethyl ether, acetone, ethanol, and ethylene glycol.

[0051] A biodegradable polymer modified with acrylate groups was obtained by drying.

[0052] The molar ratio of acrylate-based reaction reagents to modifiable groups on the side chains of biodegradable polymers is 0.0001–1, and the concentration is 1%–70%; the concentration of the biodegradable polymer modified with acrylate groups in the polyvinyl alcohol composition is 1%–20%.

[0053] S3. Preparation of hydrogel: The modified polyvinyl alcohol, biodegradable polymer, photoinitiator and good solvent are added into a stirred tank in proportion and heated and mechanically stirred until completely dissolved.

[0054] The photoinitiator includes one of Irgacure 2959, Irgacure 1173, riboflavin RF, eosin EY (tetrabromofluorescein), lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), and sodium phenyl-2,4,6-trimethylbenzoylphosphonate (NAP), and is used in an amount of 0.5% to 2% of the mass of the mercapto-modified polyvinyl alcohol. The liquid is pressurized and filtered, then squeezed into a degassing vessel and degassed under vacuum to obtain a homogeneous colloid.

[0055] The temperature of the filtrate squeezed into the degassing kettle is set to 40-150℃, and the vacuum degassing time is 3-10h.

[0056] Pour the homogeneous adhesive liquid into a rectangular mold and place it in a coagulation bath to solidify and shape.

[0057] The coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether; the temperature of the coagulation bath is -40 to 20°C; the ultraviolet light is configured with a wavelength of 200 to 400 nm, an intensity of 50 to 100 W, and an ultraviolet light irradiation time of 10 to 120 s.

[0058] Subsequently, rapid photocrosslinking is performed by irradiation with ultraviolet light. Finally, after stretching, heat setting and washing, a biodegradable and rapidly photocrosslinkable high-strength polyvinyl alcohol hydrogel is obtained.

[0059] The stretching is 1 to 30 times, the heat setting temperature is 80 to 200℃, and the washing temperature is 50 to 90℃.

[0060] Example B further narrows the range of relevant parameters based on Example A, making the proportions of each component and reaction conditions more coordinated, which is beneficial to improving the stability of the reaction process and giving the hydrogel better molding effect and comprehensive performance.

[0061] Example C: In this embodiment, the raw materials, basic steps, and post-processing methods for preparing the hydrogel are the same as in Example A. The only difference is that the preparation parameters have been adjusted. Unless otherwise specified, all contents refer to Example A.

[0062] Specifically, a method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel includes the following steps: S1. Preparation of mercapto-modified polyvinyl alcohol: Polyvinyl alcohol is dissolved in a solvent to prepare a polyvinyl alcohol solution.

[0063] The polyvinyl alcohol has a dissolution temperature of 80–100°C and a concentration of 5%–15% in the prepared polyvinyl alcohol solution. The solvent includes one or more of water, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

[0064] Subsequently, a thiolizing agent was added and reacted under the catalysis of an acidic reagent to obtain thiol-modified polyvinyl alcohol.

[0065] The thiolated agent is γ-thiobutyrolactone.

[0066] The acidic reagent is sulfuric acid; the molar ratio of the thiol-modified reagent solution and the acidic reagent solution to the hydroxyl side chain of polyvinyl alcohol is 0.01 to 0.5, and the concentration is 10% to 30%; the molecular weight of the thiol-modified polyvinyl alcohol is 120,000 to 150,000, the degree of alcoholysis is 90% to 97%, and the concentration of the thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition is 20% to 40%.

[0067] S2. Preparation of acrylate-modified biodegradable polymers: Dissolve the biodegradable polymer in a good solvent to prepare a solution.

[0068] The preferred solvent is water, and the concentration of the solution prepared by dissolving the biodegradable polymer in the preferred solvent is 1% to 20%.

[0069] Stir mechanically until completely dissolved, add acrylate-based reaction reagent dropwise, stir mechanically until the reaction is complete, and then wash the reaction solution in a poor solvent.

[0070] The acrylate group reactant is methacryloyl chloride; the molar ratio of the acrylate group reactant to the modifiable group on the side chain of the biodegradable polymer is 0.0001 to 1, and the concentration is 1% to 70%; unsuitable solvents include one or more of n-hexane, cyclohexane, petroleum ether, toluene, dichloromethane, chloroform, ethyl acetate, diethyl ether, acetone, ethanol, and ethylene glycol.

[0071] A biodegradable polymer modified with acrylate groups was obtained by drying.

[0072] The molar ratio of acrylate-based reaction reagents to modifiable groups on the side chains of biodegradable polymers is 0.01–0.5, and the concentration is 5%–30%; the concentration of the biodegradable polymer modified with acrylate groups in the polyvinyl alcohol composition is 5%–10%.

[0073] S3. Preparation of hydrogel: The modified polyvinyl alcohol, biodegradable polymer, photoinitiator and good solvent are added into a stirred tank in proportion and heated and mechanically stirred until completely dissolved.

[0074] The photoinitiator was Irgacure 2959, used at a rate of 0.8% to 1.5% of the mass of the mercapto-modified polyvinyl alcohol. The liquid is pressurized and filtered, then squeezed into a degassing vessel and degassed under vacuum to obtain a homogeneous colloid.

[0075] The temperature of the filtrate squeezed into the degassing kettle is set to 60-90℃, and the vacuum degassing time is 6-24h.

[0076] Pour the homogeneous adhesive liquid into a rectangular mold and place it in a coagulation bath to solidify and shape.

[0077] The coagulation bath component is ethylene glycol monomethyl ether, and the temperature of the coagulation bath is -30 to -10℃; the ultraviolet light configuration is a wavelength of 365nm, an intensity of 80W, and an ultraviolet light irradiation time of 30s to 90s.

[0078] Subsequently, rapid photocrosslinking is performed by irradiation with ultraviolet light. Finally, after stretching, heat setting and washing, a biodegradable and rapidly photocrosslinkable high-strength polyvinyl alcohol hydrogel is obtained.

[0079] The stretching is 5 to 10 times, the heat setting temperature is 140 to 180℃, and the washing temperature is 80 to 95℃.

[0080] Example C further optimizes the range of values ​​for relevant parameters based on Example B, making the reaction conditions more suitable and further improving the molding uniformity, structural stability and performance of the hydrogel.

[0081] The following examples all follow the basic scope of Example B, with adjustments made to one or a few parameters to demonstrate the adjustability and effects of the present invention. Specifically, the polyvinyl alcohol derivative concentration refers to the concentration of thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition; the thiol substitution rate refers to the percentage value of the molar ratio of the thiol-modifying reagent solution and the acidic reagent solution to the hydroxyl groups on the side chain of polyvinyl alcohol; the degree of substitution of acrylate groups refers to the percentage value of the molar ratio of the acrylate-group reactant to the modifiable groups on the side chain of the degradable polymer; and the performance data are representative values ​​from actual tests.

[0082] Example 1: The concentration of polyvinyl alcohol derivative was 15%, the mercaptolactone was γ-thiobutyrolactone, the sulfhydryl substitution rate was 8%, the biodegradable polymer was polyethylene glycol, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 12%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0083] Performance: Biodegradation time 145 days, mass expansion rate 35%, maximum tensile strength 55.2 MPa, maximum elongation 520%, cell viability 96.50%.

[0084] Example 2: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 10%, the biodegradable polymer was polyethylene glycol, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 15%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0085] Performance: Biodegradation time 350 days, mass expansion rate 28%, maximum tensile strength 58.5 MPa, maximum elongation 480%, cell viability 97.20%. (With prolonged biodegradation time, the mass expansion rate is somewhat reduced.) Example 3: The concentration of polyvinyl alcohol derivative was 25%, the sulfhydrylating agent was δ-thiovalactone, the sulfhydryl substitution rate was 12%, the biodegradable polymer was gelatin, the acrylate group was methacrylic anhydride, the acrylate group substitution degree was 18%, and the ultraviolet light configuration was 365nm wavelength, 50W intensity, and 90s irradiation time.

[0086] Performance: Biodegradation time 25 days, mass expansion rate 31%, maximum tensile strength 52.4 MPa, maximum elongation 610%, cell viability 98.80%. (Relatively fast biodegradation rate, high maximum elongation and cell viability.) Example 4: The concentration of polyvinyl alcohol derivative was 30%, the sulfhydrylating agent was δ-thiovalactone, the sulfhydryl substitution rate was 15%, the biodegradable polymer was gelatin, the acrylate group was methacrylic anhydride, the acrylate group substitution degree was 20%, and the ultraviolet light configuration was 365nm wavelength, 50W intensity, and 90s irradiation time.

[0087] Performance: Biodegradation time 30 days, mass expansion rate 29%, maximum tensile strength 54.8 MPa, maximum elongation 560%, cell viability 98.50%. (Maintaining a relatively fast biodegradation rate and a high maximum elongation.) Example 5: The concentration of polyvinyl alcohol derivative was 35%, the sulfhydrylating agent was ε-thiocaprolactone, the sulfhydryl substitution rate was 18%, the biodegradable polymer was hyaluronic acid, the acrylate group was acrylic anhydride, the acrylate group substitution degree was 25%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 45s irradiation time.

[0088] Performance: Biodegradation time 18 days, mass expansion rate 42%, maximum tensile strength 51.2 MPa, maximum elongation 680%, cell viability 99.10%. (Fast biodegradation, high maximum elongation and cell viability, but relatively high mass expansion rate.) Example 6: The concentration of polyvinyl alcohol derivative was 40%, the sulfhydrylating agent was ε-thiocaprolactone, the sulfhydryl substitution rate was 20%, the biodegradable polymer was hyaluronic acid, the acrylate group was acrylic anhydride, the acrylate group substitution degree was 30%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 45s irradiation time.

[0089] Performance: Biodegradation time 22 days, mass expansion rate 38%, maximum tensile strength 53.6 MPa, maximum elongation 630%, cell viability 99.30%. (Relatively fast biodegradation rate and high cell viability.) Example 7: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was sodium thiosulfate with a sulfhydryl substitution rate of 10%, the biodegradable polymer was sodium alginate oxide, the acrylate group was acryloyl chloride with a acrylate group substitution degree of 15%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0090] Performance: Biodegradation time 15 days, mass expansion rate 26%, maximum tensile strength 56.5 MPa, maximum elongation 500%, cell viability 95.80%. (Relatively fast biodegradation while maintaining good mechanical properties.) Example 8: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was α-lipoic acid, the sulfhydryl substitution rate was 10%, the biodegradable polymer was poloxamer, the acrylate group was cinnamyl chloride, the acrylate group substitution degree was 15%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0091] Performance: Biodegradation time 420 days, mass expansion rate 21%, maximum tensile strength 57.8 MPa, maximum elongation 450%, cell viability 96.00%. (Relatively long biodegradation time and relatively low mass expansion rate.) Example 9: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 15%, the biodegradable polymer was silk fibroin, the acrylate group was glycidyl methacrylate, the acrylate group substitution degree was 20%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 30s irradiation time.

[0092] Performance: Biodegradation time 180 days, mass expansion rate 24%, maximum tensile strength 62.1 MPa, maximum elongation 410%, cell viability 97.50%. (High maximum tensile strength, low mass expansion rate.) Example 10: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 20%, the biodegradable polymer was dextran, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 25%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 30s irradiation time.

[0093] Performance: Biodegradation time 38 days, mass expansion rate 27%, maximum tensile strength 59.3 MPa, maximum elongation 490%, cell viability 96.80%. (It combines rapid biodegradation with good mechanical properties.) Example 11: The concentration of polyvinyl alcohol derivative was 30%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 25%, the biodegradable polymer was chitosan, the acrylate group was methacrylic anhydride, the acrylate group substitution degree was 30%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0094] Performance: Biodegradation time 55 days, mass expansion rate 19%, maximum tensile strength 64.5 MPa, maximum elongation 380%, cell viability 95.50%. (Low mass expansion rate, high maximum tensile strength.) Example 12: The concentration of polyvinyl alcohol derivative was 10%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 5%, the biodegradable polymer was polyethylene glycol, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 10%, and the ultraviolet light configuration was 365nm wavelength, 50W intensity, and 120s irradiation time.

[0095] Performance: Biodegradation time 128 days, mass expansion rate 45%, maximum tensile strength 48.5 MPa, maximum elongation 750%, cell viability 98.20%. (High maximum elongation, but high mass expansion rate and relatively low maximum tensile strength.) Example 13: The concentration of polyvinyl alcohol derivative was 15%, the sulfhydrylating agent was ε-thiocaprolactone, the sulfhydryl substitution rate was 8%, the biodegradable polymer was gelatin, the acrylate group was acrylic anhydride, the acrylate group substitution degree was 15%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0096] Performance: Biodegradation time 20 days, mass expansion rate 33%, maximum tensile strength 49.8 MPa, maximum elongation 720%, cell viability 99.00%. (Fast biodegradation rate, high maximum elongation and cell viability.) Example 14: The concentration of polyvinyl alcohol derivative was 25%, the sulfhydrylating agent was δ-thiovalactone, the sulfhydryl substitution rate was 12%, the biodegradable polymer was hyaluronic acid, the acrylate group was cinnamyl chloride, the acrylate group substitution degree was 20%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0097] Performance: Biodegradation time 26 days, mass expansion rate 25%, maximum tensile strength 60.4 MPa, maximum elongation 430%, cell viability 98.60%. (It combines relatively fast biodegradation rate, low mass expansion rate, and high maximum tensile strength.) Example 15: The concentration of polyvinyl alcohol derivative was 30%, the sulfhydrylating agent was α-lipoic acid, the sulfhydryl substitution rate was 15%, the biodegradable polymer was sodium alginate oxide, the acrylate group was acryloyl chloride, the acrylate group substitution degree was 22%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 45s irradiation time.

[0098] Performance: Biodegradation time 23 days, mass expansion rate 20%, maximum tensile strength 61.6 MPa, maximum elongation 400%, cell viability 96.20%. (Relatively fast biodegradation rate, low mass expansion rate, and high maximum tensile strength.) Example 16: The concentration of polyvinyl alcohol derivative was 35%, the sulfhydrylating agent was sodium thiosulfate with a sulfhydryl substitution rate of 18%, the biodegradable polymer was silk fibroin, the acrylate group was glycidyl methacrylate with a acrylate group substitution degree of 28%, and the ultraviolet light configuration was 365nm wavelength, 100W intensity, and 45s irradiation time.

[0099] Performance: Biodegradation time 210 days, mass expansion rate 18%, maximum tensile strength 65.8 MPa, maximum elongation 350%, cell viability 97.00%. (Low mass expansion rate, high maximum tensile strength.) Example 17: The concentration of polyvinyl alcohol derivative was 40%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 20%, the biodegradable polymer was poloxamer, the acrylate group was methacrylic anhydride, the acrylate group substitution degree was 30%, and the ultraviolet light configuration was 365nm wavelength, 50W intensity, and 90s irradiation time.

[0100] Performance: Biodegradation time 650 days, mass expansion rate 30%, maximum tensile strength 68.2 MPa, maximum elongation 310%, cell viability 95.10%. (The biodegradation time is significantly prolonged, and the maximum tensile strength is high, but the maximum elongation is somewhat reduced.) Example 18: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 10%, the biodegradable polymer was dextran, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 15%, and the ultraviolet light configuration was 254nm wavelength, 50W intensity, and 60s irradiation time.

[0101] Performance: Biodegradation time 40 days, mass expansion rate 26%, maximum tensile strength 58.1 MPa, maximum elongation 470%, cell viability 96.50%. (It still exhibits good overall performance at 254 nm wavelength.) Example 19: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was ε-thiocaprolactone, the sulfhydryl substitution rate was 12%, the biodegradable polymer was chitosan, the acrylate group was methacrylic anhydride, the acrylate group substitution degree was 18%, and the ultraviolet light configuration was 254nm wavelength, 50W intensity, and 60s irradiation time.

[0102] Performance: Biodegradation time 50 days, mass expansion rate 29%, maximum tensile strength 59.5 MPa, maximum elongation 440%, cell viability 96.10%. (Maintains good mechanical properties at 254 nm wavelength.) Example 20: The concentration of polyvinyl alcohol derivative was 25%, the sulfhydrylating agent was δ-thiovalactone, the sulfhydryl substitution rate was 15%, the biodegradable polymer was polyethylene glycol, the acrylate group was acrylic anhydride, the acrylate group substitution degree was 20%, and the ultraviolet light configuration was 400nm wavelength, 100W intensity, and 60s irradiation time.

[0103] Performance: Biodegradation time 380 days, mass expansion rate 34%, maximum tensile strength 57.2 MPa, maximum elongation 510%, cell viability 97.40%. (Exhibits a relatively long biodegradation time and a high maximum elongation at 400 nm wavelength.) Example 21: The concentration of polyvinyl alcohol derivative was 25%, the sulfhydrylating agent was α-lipoic acid, the sulfhydryl substitution rate was 18%, the biodegradable polymer was gelatin, the acrylate group was acryloyl chloride, the acrylate group substitution degree was 25%, and the ultraviolet light configuration was 400nm wavelength, 100W intensity, and 60s irradiation time.

[0104] Performance: Biodegradation time 32 days, mass expansion rate 39%, maximum tensile strength 56.8 MPa, maximum elongation 530%, cell viability 98.30%. (Relatively fast biodegradation rate, high maximum elongation and cell viability.) Example 22: The concentration of polyvinyl alcohol derivative was 30%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 20%, the biodegradable polymer was hyaluronic acid, the acrylate group was cinnamyl chloride, the acrylate group substitution degree was 30%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 90s irradiation time.

[0105] Performance: Biodegradation time 24 days, mass expansion rate 36%, maximum tensile strength 54.5 MPa, maximum elongation 590%, cell viability 98.90%. (Relatively fast biodegradation rate, high maximum elongation and cell viability.) Example 23: The concentration of polyvinyl alcohol derivative was 15%, the sulfhydrylating agent was sodium thiosulfate with a sulfhydryl substitution rate of 8%, the biodegradable polymer was sodium alginate oxide, the acrylate group was glycidyl methacrylate with a substitution degree of 12%, and the ultraviolet light configuration was 365nm wavelength, 50W intensity, and 120s irradiation time.

[0106] Performance: Biodegradation time 36 days, mass expansion rate 22%, maximum tensile strength 51.5 MPa, maximum elongation 650%, cell viability 96.40%. (Low mass expansion rate, high maximum elongation.) Example 24: The concentration of polyvinyl alcohol derivative was 35%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 25%, the biodegradable polymer was silk fibroin, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 35%, and the ultraviolet light configuration was 365nm wavelength, 150W intensity, and 20s irradiation time.

[0107] Performance: Biodegradation time 246 days, mass expansion rate 15%, maximum tensile strength 66.5 MPa, maximum elongation 330%, cell viability 96.90%. (Low mass expansion rate, high maximum tensile strength.) Example 25: Polyvinyl alcohol derivative concentration 40%, thiocaprolactone as the sulfhydrylating agent, 30% sulfhydryl substitution rate, poloxamer as the biodegradable polymer, methacrylic anhydride as the acrylate group, 40% acrylate group substitution degree, and ultraviolet light configuration of wavelength 365nm, intensity 150W, and irradiation time 20s.

[0108] Performance: Biodegradation time 770 days, mass expansion rate 27%, maximum tensile strength 70.1 MPa, maximum elongation 280%, cell viability 94.80%. (High maximum tensile strength and significantly prolonged biodegradation time, but reduced maximum elongation and cell viability.) The following comparative examples are used to compare the effects of existing technologies or those lacking key steps.

[0109] Comparative Example 1: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 10%, the biodegradable polymer was polyethylene glycol, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 15%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0110] Performance: Biodegradation time 342 days, mass expansion rate 58%, maximum tensile strength 41.5 MPa, maximum elongation 150%, cell viability 96.00%. (High mass expansion rate, low maximum tensile strength and maximum elongation.) Comparative Example 2: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type γ-thiobutyrolactone, sulfhydryl substitution rate 10%, biodegradable polymer type polyethylene glycol, acrylate group type methacryloyl chloride, acrylate group substitution degree 15%, no ultraviolet irradiation.

[0111] Performance: Biodegradation time 310 days, mass expansion rate 50%, maximum tensile strength 40.8 MPa, maximum elongation 80%, cell viability 97.50%. (Maximum elongation is significantly reduced, while mass expansion rate is increased.) Comparative Example 3: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0112] Performance: Biodegradation time 348 days, mass expansion rate 49%, maximum tensile strength 42.2 MPa, maximum elongation 850%, cell viability 96.80%. (High maximum elongation, but high mass expansion rate and low maximum tensile strength.) Comparative Example 4: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 2s.

[0113] Performance: Biodegradation time 315 days, mass expansion rate 65%, maximum tensile strength 43.5 MPa, maximum elongation 210%, cell viability 96.50% (significantly increased mass expansion rate.) Comparative Example 5: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 200W, irradiation time 300s.

[0114] Performance: Biodegradation time 380 days, mass expansion rate 12%, maximum tensile strength 51.0 MPa, maximum elongation 120%, cell viability 65.20%. (Maximum elongation and cell viability are significantly reduced.) Comparative Example 6: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 200nm, intensity 20W, irradiation time 5s.

[0115] Performance: Biodegradation time 320 days, mass expansion rate 60%, maximum tensile strength 44.2 MPa, maximum elongation 240%, cell viability 95.80%. (High mass expansion rate, low maximum tensile strength.) Comparative Example 7: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type γ-thiobutyrolactone, sulfhydryl substitution rate 10%, no biodegradable polymer added, no acrylate groups and no acrylate group substitution degree, UV light configuration 365nm wavelength, 80W intensity, irradiation time 60s.

[0116] Performance: Biodegradation time 60 days, mass expansion rate 31%, maximum tensile strength 52.5 MPa, maximum elongation 380%, cell viability 90.50% (cell viability is somewhat reduced.) Comparative Example 8: The concentration of polyvinyl alcohol derivative was 20%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 10%, no biodegradable polymers were added, the type of acrylate groups and the degree of substitution of acrylate groups were both zero, and the ultraviolet light configuration was 365nm wavelength, 80W intensity and 180s irradiation time.

[0117] Performance: Biodegradation time 65 days, mass expansion rate 28%, maximum tensile strength 55.0 MPa, maximum elongation 320%, cell viability 88.40%. (Maximum elongation and cell viability are further reduced.) Comparative Example 9: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0118] Performance: Biodegradation time 360 ​​days, mass expansion rate 25%, maximum tensile strength 59.5 MPa, maximum elongation 410%, cell viability 85.20%. (Good mechanical properties, but significantly low cell viability.) Comparative Example 10: Polyvinyl alcohol derivative concentration 0.50%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 2%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 5%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0119] Performance: Biodegradation time 305 days, mass expansion rate 80%, maximum tensile strength 40.5 MPa, maximum elongation 110%, cell viability 98.50%. (The expansion rate is significantly increased, and the mechanical properties decrease.) Comparative Example 11: The concentration of polyvinyl alcohol derivative was 95%, the sulfhydrylating agent was γ-thiobutyrolactone, the sulfhydryl substitution rate was 40%, the biodegradable polymer was polyethylene glycol, the acrylate group was methacryloyl chloride, the acrylate group substitution degree was 50%, and the ultraviolet light configuration was 365nm wavelength, 80W intensity, and 60s irradiation time.

[0120] Performance: Biodegradation time 390 days, mass expansion rate 90%, maximum tensile strength 75.0 MPa, maximum elongation 50%, cell viability 72.40%. (Although the maximum tensile strength is high, the mass expansion rate, maximum elongation, and cell viability are significantly deteriorated.) Comparative Example 12: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 0.50%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0121] Performance: Biodegradation time 312 days, mass expansion rate 75%, maximum tensile strength 41.8 MPa, maximum elongation 900%, cell viability 97.80%. (Although the maximum elongation is high, the mass expansion rate is relatively high, and the maximum tensile strength is relatively low.) Comparative Example 13: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 60%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 15%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0122] Performance: Biodegradation time 420 days, mass expansion rate 11%, maximum tensile strength 68.5 MPa, maximum elongation 80%, cell viability 68.50%. (Although the mass expansion rate is low and the maximum tensile strength is high, the maximum elongation and cell viability are significantly reduced.) Comparative Example 14: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 0.50%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0123] Performance: Biodegradation time 310 days, mass expansion rate 85%, maximum tensile strength 41.2 MPa, maximum elongation 850%, cell viability 98.00%. (Although the maximum elongation is high, the mass expansion rate is relatively high, and the maximum tensile strength is relatively low.) Comparative Example 15: Polyvinyl alcohol derivative concentration 20%, sulfhydrylating agent type is γ-thiobutyrolactone, sulfhydryl substitution rate is 10%, biodegradable polymer type is polyethylene glycol, acrylate group type is methacryloyl chloride, acrylate group substitution degree is 60%, ultraviolet light configuration is wavelength 365nm, intensity 80W, irradiation time 60s.

[0124] Performance: Biodegradation time 385 days, mass expansion rate 10%, maximum tensile strength 66.4 MPa, maximum elongation 95%, cell viability 70.20%. (Although the mass expansion rate is low and the maximum tensile strength is high, the maximum elongation and cell viability are significantly reduced.) Table 1. Composition of the adhesive solution in each preparation example and comparative example.

[0125] Table 2 Performance Comparison of Examples and Comparative Examples

[0126] As can be seen from the above embodiments and comparative examples: The hydrogels prepared in this invention employ a process of freeze-forming to construct a nanocrystalline physical cross-linked network, followed by ultraviolet light irradiation to trigger a click chemical reaction of thiol-olefins, forming a stable chemical cross-linked network. Further enhancement of molecular chain orientation is achieved through heat-setting and stretching. This synergistic effect endows the gel with excellent mechanical properties (maximum tensile strength up to 75.0 MPa) and a suitable mass swelling ratio. Simultaneously, the introduction of a biodegradable polymer not only maintains the high-strength cross-linked backbone but also imparts good biocompatibility and a controllable degradation period (15–770 days), highly meeting the clinical needs of cartilage / bone tissue engineering and skin wound dressings.

[0127] The embodiments of the present invention have been described in detail above with reference to the accompanying drawings. However, the present invention is not limited thereto. Various changes can be made within the scope of knowledge possessed by those skilled in the art without departing from the spirit of the present invention.

Claims

1. A biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel, characterized in that, It is prepared from polyvinyl alcohol, a biodegradable polymer, and a photoinitiator; The polyvinyl alcohol can react with a mercapto reagent; The biodegradable polymer reacts with an acrylate-based reactive reagent; The polyvinyl alcohol, biodegradable polymer, and photoinitiator are mixed, dissolved, solidified, and subjected to rapid photocrosslinking under ultraviolet light irradiation. The resulting polyvinyl alcohol hydrogel is then obtained through stretching, heat setting, and washing.

2. A method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel, characterized in that, Includes the following steps: S1. Preparation of thiol-modified polyvinyl alcohol: Polyvinyl alcohol is dissolved in a solvent to prepare a polyvinyl alcohol solution, and then a thiol-modifying agent is added and reacted under the catalysis of an acidic reagent to obtain thiol-modified polyvinyl alcohol. S2. Preparation of acrylate-modified biodegradable polymers: Dissolve the biodegradable polymer in a good solvent to prepare a solution, stir mechanically until completely dissolved, add acrylate-modified reagents dropwise, stir mechanically until the reaction is complete, pour the reaction solution into a poor solvent for washing, and dry to obtain acrylate-modified biodegradable polymers. S3. Preparation of hydrogel: The modified polyvinyl alcohol, biodegradable polymer, photoinitiator and good solvent are added into a stirred tank in proportion, heated and mechanically stirred until completely dissolved, filtered under pressure, and the filtrate is squeezed into a degassing tank and degassed under vacuum to obtain a homogeneous solution. The homogeneous solution is poured into a rectangular mold and placed in a coagulation bath to solidify and form. Then, it is rapidly photocrosslinked by ultraviolet light irradiation. Finally, after stretching, heat setting and washing, a high-strength polyvinyl alcohol hydrogel that is biodegradable and rapidly photocrosslinkable is obtained.

3. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The polyvinyl alcohol has a dissolution temperature of 20–250°C and a concentration of 0.5%–80% in the prepared polyvinyl alcohol solution. The solvent includes one or more of water, dimethylformamide, dimethylacetamide, N-methylpyrrolidone, and dimethyl sulfoxide.

4. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 3, characterized in that, The polyvinyl alcohol has a dissolution temperature of 40–150°C and the concentration of the prepared polyvinyl alcohol solution is 1%–40%.

5. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 3, characterized in that, The polyvinyl alcohol has a dissolution temperature of 80–100°C and a concentration of 5%–15% in the prepared polyvinyl alcohol solution.

6. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The thiolation reagent includes one or more of γ-thiobutyrolactone, δ-thiovalactone, ε-thiocaprolactone, homocysteine ​​thiolactone, α-lipoic acid, 3,3'-dithiodipropionic acid, cyclic thiocarbonate, thiosuccinic anhydride, protected thiolactone, and dithiolactone.

7. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 6, characterized in that, The thiolated agent is γ-thiobutyrolactone.

8. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The acidic reagents include one or more of sulfuric acid, p-toluenesulfonic acid, methanesulfonic acid, camphorsulfonic acid, hydrochloric acid, phosphoric acid, and perchloric acid; The molar ratio of the thiol-modifying reagent solution and the acidic reagent solution to the hydroxyl groups of the polyvinyl alcohol side chain is 0.0001–1, and the concentration is 1%–70%. The thiol-modified polyvinyl alcohol has a molecular weight of 6,000 to 200,000 and a degree of alcoholysis of 60% to 100%. The concentration of the thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition is 1% to 90%.

9. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 8, characterized in that, The thiol-modified polyvinyl alcohol has a molecular weight of 80,000 to 170,000, a degree of alcoholysis of 70% to 99%, and a concentration of thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition of 10% to 60%.

10. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 8, characterized in that, The acidic reagent is sulfuric acid; The molar ratio of the thiol-modifying reagent solution and the acidic reagent solution to the hydroxyl groups on the side chain of polyvinyl alcohol is 0.01–0.5, and the concentration is 10%–30%. The thiol-modified polyvinyl alcohol has a molecular weight of 120,000 to 150,000, a degree of alcoholysis of 90% to 97%, and a concentration of thiol-modified polyvinyl alcohol in the polyvinyl alcohol composition of 20% to 40%.

11. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The good solvent includes one or more of water, DMF, DMAc, NMP, and DMSO; the degradable polymer includes one or more of gelatin, hyaluronic acid, sodium alginate, poloxamer, silk fibroin, dextran, chitosan, and polyethylene glycol, and the concentration of the solution prepared by dissolving the degradable polymer in the good solvent is 0.5% to 80%.

12. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 11, characterized in that, The good solvent is water, and the concentration of the solution prepared by dissolving the degradable polymer in the good solvent is 1% to 20%.

13. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The acrylate-based reactive reagents include one or more of methacrylic anhydride, acrylic anhydride, methacryloyl chloride, acryloyl chloride, cinnamoyl chloride, and glycidyl methacrylate. The molar ratio of the acrylate-based reactive reagent to the modifiable groups on the side chains of the biodegradable polymer is 0.0001–1, and the concentration is 1%–70%. The undesirable solvents include one or more of n-hexane, cyclohexane, petroleum ether, toluene, dichloromethane, chloroform, ethyl acetate, diethyl ether, acetone, ethanol, and ethylene glycol.

14. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 13, characterized in that, The acrylate group reaction reagent is methacryloyl chloride.

15. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The molar ratio of the acrylate-based reactive reagent to the modifiable groups on the side chains of the biodegradable polymer is 0.0001–1, and the concentration is 1%–70%. The concentration of the acrylate-modified biodegradable polymer in the polyvinyl alcohol composition is 0.5% to 30%.

16. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 15, characterized in that, The concentration of the acrylate-modified biodegradable polymer in the polyvinyl alcohol composition is 1% to 20%.

17. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 15, characterized in that, The molar ratio of the acrylate-based reactive reagent to the modifiable groups on the side chains of the biodegradable polymer is 0.01–0.5, and the concentration is 5%–30%. The concentration of the acrylate-modified biodegradable polymer in the polyvinyl alcohol composition is 5% to 10%.

18. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The photoinitiator includes one of Irgacure 2959, Irgacure 1173, riboflavin RF, eosin EY (tetrabromofluorescein), lithium phenyl-2,4,6-trimethylbenzoylphosphonate (LAP), and sodium phenyl-2,4,6-trimethylbenzoylphosphonate (NAP), and is used in an amount of 0.1% to 5% of the mass of the mercapto-modified polyvinyl alcohol.

19. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 18, characterized in that, The amount of photoinitiator used is 0.005wt% to 5wt% of the mass of the mercapto-modified polyvinyl alcohol.

20. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 18, characterized in that, The photoinitiator is Irgacure 2959, and the amount used is 0.8% to 1.5% of the mass of the mercapto-modified polyvinyl alcohol.

21. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 2, characterized in that, The temperature of the filtrate squeezed into the degassing vessel is set to 0-200℃, and the vacuum degassing time is 1h-72h. The coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and the temperature of the coagulation bath is -60 to 70°C. The ultraviolet light is configured with a wavelength of 200-400nm, an intensity of 20-150W, and an irradiation time of 5s-180s; The stretching is 0.1 to 50 times, the heat setting temperature is 20 to 300°C, and the water washing temperature is 10 to 100°C.

22. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 21, characterized in that, The temperature of the filtrate squeezed into the degassing kettle is set to 40-150°C, and the vacuum degassing time is 3-10 hours. The coagulation bath components include one or more of ethylene glycol, ethylene glycol monomethyl ether, ethylene glycol monoethyl ether, ethylene glycol monobutyl ether, diethylene glycol monomethyl ether, and propylene glycol monomethyl ether, and the temperature of the coagulation bath is -40 to 20°C. The ultraviolet light is configured with a wavelength of 200-400nm, an intensity of 50-100W, and an irradiation time of 10s-120s; The stretching is 1 to 30 times, the heat setting temperature is 80 to 200°C, and the washing temperature is 50 to 90°C.

23. The method for preparing a biodegradable, swelling-resistant, high-strength polyvinyl alcohol hydrogel according to claim 21, characterized in that, The temperature of the filtrate squeezed into the degassing kettle is set to 60-90°C, and the vacuum degassing time is 6-24 hours. The coagulation bath component is ethylene glycol monomethyl ether, and the temperature of the coagulation bath is -30 to -10°C. The ultraviolet light is configured with a wavelength of 365nm, an intensity of 80W, and an irradiation time of 30s to 90s; The stretching is 5 to 10 times, the heat setting temperature is 140 to 180°C, and the washing temperature is 80 to 95°C.